A scanning electron microscopy investigation of the precision of three orthodontic bracket slot systems - Mohammed Nahidh; Yassir A. Yassir; Maria Maddalena Marrapodi; Marco Di Blasio; Vincenzo Ronsivalle; Marco Cicciù; Giuseppe Minervini (BMC, 2024)
Abstract Objective One of the most imprortant factors in achieving ideal teeth positions is the precision of the slot dimensions of orthodontic brackets into the archwires are inserted.This study aimed to assess the accuracy of the dimensions of orthodontic bracket slots and molar buccal tube apertures and to compare them with the specifications provided by the manufacturers. Method A total of sixty brackets and ten molar buccal tubes with varying slot heights were examined using a scanning electron microscope from the mesial side. The dimensions and morphology of these bracket slots and buccal tubes apertures were assessed using the AutoCAD Software. A one-sample t-test was conducted to compare the measurements with the values provided by the manufacturer. Results The findings of the present study indicated that the height of the measured bracket slots and buccal tube apertures dimensions were significantly larger than the actual dimensions and exhibiting divergent walls. On the other hand, the depth of the brackets slots showed significantly smaller values than the actual one. Conclusion A need for careful consideration when selecting a commercially accessible brand for everyday use is essential as certain materials may not meet acceptable standards.